Testing the Analytical Rumination Hypothesis: Exploring the Longitudinal Effects of Problem Solving Analysis on Depression - Sevcikova, Marcela; Maslej, Marta M.; Stipl, Jiri; Andrews, Paul W.; Pastrnak, Martin; Vechetova, Gabriela; Bartoskova, Magda; Preiss, Marek (Frontiers in Psychology, 2020)
Depression is a mental health condition for which individuals commonly seek treatment. However, depressive episodes often resolve on their own, i.e. without treatment. One evolutionary perspective, the Analytical rumination hypothesis, suggests that depression occurs in response to complex problems. According to this perspective, depressive symptoms promote analytical rumination, i.e., distraction-resistant thoughts about the causes of problems (causal analysis; CA) and how they can be solved (problem-solving analysis; PSA). By helping individuals solve complex problems, analytical rumination may contribute to remission from depression. The aim of this study was to investigate 1) whether clinically-depressed individuals have more complex problems and engage in more CA and PSA than non-depressed; and 2) the effects of CA and PSA on decreases in problem complexity, depressive symptoms and remission from the depression. Samples of 85 patients treated for depression with antidepressants and psychotherapy and 49 healthy subjects were assessed three times over a four-month period (at Weeks 1, 5, and 16). At each assessment, they completed measures of depression, analytical rumination, and problem complexity. Depressed individuals reported having more complex problems and engaging in more CA than non-depressed participants. The two groups engaged in a similar degree of PSA. Findings from a multiple regression suggested that more PSA at Week 1 was related to a decrease in depressive symptoms at Week 5, even after controlling for baseline depression, problem number, and complexity. PSA at Week 1 did not predict the remission after hospitalization or at follow-up; however, having less complex problems at the baseline made it more likely a patient would later remit. Engaging in more CA or PSA at Week 1 did not affect perceived problem complexity at Week 5 or at follow-up. However, these findings were not statistically significant when influential observations (or outliers) were included in the analysis. Our findings suggest that PSA may contribute to a decrease in symptoms of depression over time. However, alleviations in problem complexity and remission might only be achieved if problems are initially less complex. Future directions involve exploring how PSA might contribute to decreases in depressive symptoms and other mechanisms underlying remission from depression.